The Effect of Inflation, the Rupiah Exchange Rate, the BI Interest Rate, and Sales Growth on Stock Prices in the Jakarta Islamic Index (JII) 2020-2024 - Kadek Kurnia Ningsih; Endang Asliana; Artie Arditha Rachman (Jurnal Pengabdian Nusantara, 2026)
This study aims to analyze the influence of macroeconomic factors namely inflation, the rupiah exchange rate, and the BI interest rate and a micro-fundamental factor, sales growth, on stock prices of companies listed in the Jakarta Islamic Index (JII) during the 2020–2024 period. Using a quantitative method and SPSS 25, the research data were selected through purposive sampling. The test results indicate that inflation has a significant effect on stock prices, whereas the rupiah exchange rate, BI interest rate, and sales growth do not show a significant partial effect. However, the four variables are proven to have a simultaneous effect on JII stock price movements. These findings emphasize that stock price dynamics are influenced not only by macroeconomic conditions but also by the internal performance of companies. Therefore, a comprehensive understanding of both external factors and company fundamentals is crucial for investors, firms, and policymakers in responding to capital market volatility in the post-pandemic period.